Best books for children, supplement to the 8th edition preschool through grade 6 - Barr, Catherine 1951- (Children's and young adult literature reference series., 2007)
Offers five thousand thematically arranged reviews and recommendations for children's books up to the sixth grade, each of which includes an annotation, review citations, and bibliographic data.